Wheatgrass extract imparts neuroprotective actions against scopolamine-induced amnesia in mice. Issue 16 (21st July 2022) - Katiyar, Parul; Singh Rathore, Aaina; Banerjee, Somesh; Nathani, Sandip; Zahra, Walia; Singh, Surya Pratap; Sircar, Debabrata; Roy, Partha
Abstract : The rich and diverse phytoconstituents of wheatgrass have established it as a natural antioxidant and detoxifying agent. Abstract : The rich and diverse phytoconstituents of wheatgrass have established it as a natural antioxidant and detoxifying agent. The anti-inflammatory potential of wheatgrass has been studied extensively. However, the neuroprotective potential of wheatgrass has not been studied in depth. In this study, we investigated the neuroprotective response of wheatgrass against age-related scopolamine-induced amnesia in mice. Scopolamine is an established anticholinergic drug that demonstrates the behavioural and molecular characteristics of Alzheimer's disease. In the current study, wheatgrass extracts (prepared from 5 and 7 day old plantlets) were administered to scopolamine-induced memory deficit mice. The Morris water maze (MWM) and Y-maze tests demonstrated that wheatgrass treatment improves the behavior and simultaneously enhances the memory of amnesic mice. We further evaluated the expression of neuroinflammation related genes and proteins in the hippocampal region of mice. Wheatgrass significantly upregulated the mRNA and protein expression of neuroprotective markers such as BDNF and CREB in scopolamine-induced mice. Simultaneously, wheatgrass also downregulated the expression of inflammatory markers such as TNF-α and tau genes in these mice. The treatment of scopolamine-induced memory impaired mice with wheatgrass resulted in an elevation in the level of the phosphorylated form of ERK and Akt proteins. Wheatgrass treatment of mice also regulated the phosphorylation of tau protein and simultaneously prevented its aggregation in the hippocampal region of the brain. Overall, this study suggests the therapeutic potential of wheatgrass in the treatment of age-related memory impairment, possibly through the involvement of ERK/Akt-CREB-BDNF pathway and concomitantly ameliorating the tau-related pathogenesis.